Sanksi Pidana Perzinahan Akibat Adanya Delik Aduan dari Pihak yang Dirugikan Menurut Pasal 284 Kuhp - Muhammad Ridho Muttaqien; Anyelir Puspa Kemala (Syntax Corporation, 2023)
This study aims to obtain information and analyze the law regarding the criminal sanctions for adultery due to complaints from the injured party according to Article 284 paragraph (1) of the Criminal Code. One of the regulated behaviors related to adultery in marriage is adultery in the context of Islamic law and overspel in criminal law literature. The rampant adultery in public life has tarnished the existence of a sacred bond in marriage.